Polymorphonuclear neutrophil response to Burkholderia pseudomallei in patients with diabetes mellitus - Mazumder, Sraboni; Barai, Lovely; Jilani, Md Shariful Alam; Islam, KM Shahidul; Haq, Jalaluddin Ashraful (IMC Journal of Medical Science, 2020)
Background and objectives: Burkholderia pseudomallei is the causative agent of melioidosis, a potentially fatal disease endemic in Bangladesh. Diabetes mellitus (DM) is a risk factor for increased susceptibility to B. pseudomallei infection. A few studies have been conducted to identify the underlying immunological mechanism responsible for increased susceptibility of individuals with diabetes mellitus to B. pseudomallei infection. The present study investigated the polymorphonuclear neutrophil (PMN) response to B. pseudomallei in terms of phagocytosis and early respiratory burst in individuals with diabetes mellitus. Materials and Methods: A total of 5 cases of DM and 5 age and sex matched non-diabetic healthy individuals were enrolled in the study to determine the early respiratory burst and phagocytic ability of PMN to B. pseudomallei. The effect of B. pseudomallei on phagocytic ability and early respiratory burst of PMN was determined by phagocytic assay and nitroblue tetrazolium (NBT) test respectively. The response of PMN treated with B. pseudomallei was compared with that of Escherichia coli. Results: There was no significant (p>0.05) difference in phagocytosis of B. pseudomallei by PMN between diabetic and non-diabetic cases (21.8±4.64 percent vs 29.25±5.5 percent). But in both diabetic and non-diabetic cases, significantly (p˂0.05 and p˂0.01) reduced rate of phagocytosis of B. pseudomallei by PMN was observed compared to E. coli (21.8±4.64 vs 65±5.36; 29.25±5.5 vs 71.25±5.59). Similar results were obtained in terms of phagocytic index. Mean percentage of formazan positive PMN from diabetic cases was not significantly different (p>0.05) from non-diabetic healthy cases when cells were treated with B. pseudomallei or E. coli. In both diabetic and healthy individuals, mean percentage of formazan positive PMN treated by B. pseudomallei was not significantly different from that by E. coli. Conclusion: The observations revealed that B. pseudomallei was equally capable of inhibiting the phagocytic ability of PMN from both diabetic and non-diabetic individuals. This anti-phagocytic property might play an important role in the pathogenesis of melioidosis. Ibrahim Med. Coll. J. 2019; 13(2): 28-34